Milk and juice a recycling romance - Brown, Meredith Crandall ca. 21. Jh (Harper, an imprint of HarperCollinsPublishers, 2021)
"Once upon a time, in a refrigerator not too far away, a jug of milk and a bottle of juice fell in love. All was bliss until Juice was taken away from its one true love and...recycled. Thus begins Milk and Juice's humorous journey through many incarnations around the world. Will they ever be reunited? Or will they stay star-crossed lovers for all eternity?"--
Keywords: Humor; Kunststoffflasche; Recycling; Trennung; Verlieben; Wiedervereinigung; Recycling (Waste, etc.) / Juvenile fiction; Love / Juvenile fiction; Recycling (Waste, etc.) / Fiction; Love / Fiction; Humorous stories; Picture books; Recyclage (Déchets, etc.) / Romans, nouvelles, etc. pour la jeunesse; Love; Recycling (Waste, etc.); Recycling / Juvenile fiction; Milk / Juvenile fiction; Orange juice / Juvenile fiction; Goal (Psychology) / Juvenile fiction; Persistence / Juvenile fiction; Recycling / Fiction; Milk / Fiction; Orange juice / Fiction; Goal (Psychology) / Fiction; Persistence / Fiction; Picture books for children; picture books; Fiction; Juvenile works; Children's stories / Pictorial works; Humorous fiction; Livres d'images; Bilderbuch